Bowel vaginoplasty in children - Sarin Yogesh; Pathak D; Sengar M (Wolters Kluwer Medknow Publications, 2006)
OBJECTIVES: To describe our experience with bowel vaginoplasty done in children. MATERIALS AND METHODS: This is a retrospective study of eight children aged 10 months to 8 years, who underwent bowel vaginoplasty over a period of 5 years (2000-2005). The indications of bowel vaginoplasty included anorectovestibular fistula (ARVF) associated with Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome (n=6) and cloaca (n=2). The bowel segment used for vaginoplasty included colon (n=3), ileum (n=2) and duplicated rectum (n=1). In two patients of ARVF associated with uterovaginal agenesis, the distal- most part of ARVF was transected at the level of peritoneal reflection and left as neovagina, whereas the proximal bowel was pulled through at the proposed neo-anal site. All the patients were advised daily home dilatation of the neo vaginal orifice with Hegar′s dilators, for a period of six weeks. RESULTS: Bowel vaginoplasty was done in eight patients. None had any significant per-operative complication. Two patients had abdominal wound dehiscence, requiring secondary suturing. Two patients had mucosal prolapse of the neovagina, which required trimming. One patient died two months after discharge, because of meningitis. Out of the eight patients, seven are in regular follow-up. Six patients have neovagina, cosmetically acceptable to the parents; all have been radiologically proven to have adequate length. One patient had unacceptable perineal appearance with nipple-like vaginal orifice and scarred perineal wound, that merits a revision. None of the patients had vaginal stenosis and excessive mucus discharge, during follow-up visits. Although post surgical results are acceptable to the parents cosmetically, the sexual and psychological outcome is yet to be assessed. Conclusions: Bowel vaginoplasty is a safe and acceptable procedure to treat the pediatric patients of uterovaginal agenesis and cloaca.